Promotion of mechanisms to strengthen vertical accountability in local governments: the case of health in Brazil - Santos, Marcus Vinicius Cunha dos; Gonçalves, Andrea de Oliveira (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: To analyze the influence of the political and professional profile of public officials on the provision of mechanisms that promote vertical accountability in the local health system in Brazil. Methodology: This qualitative study was developed in two stages. In the first stage, a structured questionnaire organized into thematic blocks was administered to 83 Municipal Health Departments, with the objective of characterizing the professional and political-party profiles of managers and respondents' perceptions regarding vertical accountability instruments. The second stage involved documentary analysis of the official websites of the corresponding 83 municipalities regarding the presence, accessibility, and functioning of vertical accountability instruments. Data were analyzed through documentary analysis and descriptive statistics, organized in electronic spreadsheets, categorized and compared. Results: There is an influence of the political and professional profile of public health managers on the improvement of vertical accountability mechanisms in local governments. The study findings show that secretaries with political party affiliation demonstrated below-average performance in offering or maintaining vertical accountability instruments compared to those without party affiliation. Regarding professional profile, results indicated better performance by health managers with educational background related to health and higher education degrees. Contributions of the study: This study provides original empirical evidence on how individual characteristics of municipal health managers—notably the absence of political party affiliation and professional training in the health field—are positively associated with the existence and effective functioning of vertical accountability mechanisms. By triangulating self-reported data with documentary verification across 83 Brazilian municipalities, the research advances beyond normative literature to demonstrate that the politicization of appointments compromises both the formal availability of these instruments and their actual capacity to promote transparency, responsiveness, and social oversight. These findings reinforce the importance of decoupling technical criteria from partisan logic in appointments to strategic positions within the Unified Health System (Sistema Único de Saúde – SUS in portuguese), thereby contributing to both theoretical debates on subnational governance and policy formulation aimed at strengthening democratic administration in public health.